The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/gcb.13352
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure reduces the response to impulsive noise in European seabass

Abstract: Human activities have changed the acoustic environment of many terrestrial and aquatic ecosystems around the globe. Mounting evidence indicates that the resulting anthropogenic noise can impact the behaviour and physiology of at least some species in a range of taxa. However, the majority of experimental studies have considered only immediate responses to single, relatively short‐term noise events. Repeated exposure to noise could lead to a heightened or lessened response. Here, we conduct two long‐term (12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 58 publications
4
59
2
1
Order By: Relevance
“…Chan et al, 2010;Meillère et al, 2015;Simpson et al, 2015Simpson et al, , 2016Shannon et al, 2016). Longer-term studies are needed to consider such aspects as compensation and changing responses (Bejder et al, 2009), because individuals may become more or less tolerant with repeated exposure (Scholik and Yan, 2001;Wale et al, 2013b;Radford et al, 2016). In terms of vocalisations, there is evidence that anthropogenic noise could lead to signallers adjusting acoustic parameters plastically (Patricelli and Blickley, 2006;Templeton et al, 2016) or alterations occurring across generations (Slabbekoorn and Ripmeester, 2008;Lowry et al, 2012), to improve the effectiveness of communication.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al, 2010;Meillère et al, 2015;Simpson et al, 2015Simpson et al, , 2016Shannon et al, 2016). Longer-term studies are needed to consider such aspects as compensation and changing responses (Bejder et al, 2009), because individuals may become more or less tolerant with repeated exposure (Scholik and Yan, 2001;Wale et al, 2013b;Radford et al, 2016). In terms of vocalisations, there is evidence that anthropogenic noise could lead to signallers adjusting acoustic parameters plastically (Patricelli and Blickley, 2006;Templeton et al, 2016) or alterations occurring across generations (Slabbekoorn and Ripmeester, 2008;Lowry et al, 2012), to improve the effectiveness of communication.…”
Section: Discussionmentioning
confidence: 99%
“…The increased oxygen uptake suggests heightened stress during exposure to pile driving (Barton, 2002). Other species, such as European eels (Anguilla anguilla) and European sea bass also increased oxygen uptake when exposed to playback of anthropogenic sounds Radford et al, 2016), whereas an in situ pile driving study using European sea bass found a decrease in oxygen uptake (Debusschere et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…The signals produced by seismic surveying have been documented to cause some fish to flee (Fewtrell & McCauley 2012), although the response to impulsive noise is reduced after repeated exposure (Radford et al 2016). Seismic signals can elicit a startle response in coral reef fishes (Boeger et al 2006) and a change in their swimming pattern, whereby individuals move to the bottom of the water column and swim faster in tighter groups (Pearson et al 1992, Fewtrell & McCauley 2012, Neo et al 2015; the latter behavior is also called atypical mass stranding in squids (Guerra et al 2004(Guerra et al , 2011.…”
Section: Sub-lethal Effectsmentioning
confidence: 99%
“…Respiration and oxygen con-sumption rates have been used as measures of direct physiological response in fish (Radford et al 2016), cephalopods (Kaifu et al 2007), and lobsters (Filiciotto et al 2014). As an example, European seabass exposed to playbacks of recordings of pile-driving and seismic surveys exhibited increased ventilation rates in relation to control individuals exposed to ambient-noise playback (Radford et al 2016).…”
Section: Sub-lethal Effectsmentioning
confidence: 99%
See 1 more Smart Citation